A study of Emotional Intelligence among Doctors - Pandey, Sandeep Kumar; Singh , Abhishek Pratap (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of the study was to investigate the emotional intelligence of Doctors of private and public hospitals. For fulfillment of this study we comprised total 160 Doctors and divide them into two groups of private hospitals (80= 40 male & 40 female) and public hospitals (80=40 male & 40 female). For assessing emotional intelligence of Doctors,Emotional Intelligence scale(MSREIS-R) constructed and standardized by Prof. Rakesh Pandey and Dr. TulikaAnand (2013) administered on them. Data was collected from different private and public Hospitals of Haridwar, Rishikesh and Dehradun district of Uttrakhand. For this study data analyzed by using parametric statistical technique (M, SD,‘t’ test and ANOVA). Results revealed significant difference in private and public Doctors. Public Doctors possess high mean of score compare to private.However, Male Doctors showed more emotionally intelligent than female. There was no interaction effect found between gender and types of hospitals on the all factors and total of emotional intelligence.